Backbone distortions in lactam‐bridged helical peptides. (9th February 2022) - Moazzam, Ali; Stanojlovic, Vesna; Hinterholzer, Arthur; Holzner, Christoph; Roschger, Cornelia; Zierer, Andreas; Wiederstein, Markus; Schubert, Mario; Cabrele, Chiara
Abstract : Side‐chain‐to‐side‐chain cyclization is frequently used to stabilize the α‐helical conformation of short peptides. In a previous study, we incorporated a lactam bridge between the side chains of Lys‐i and Asp‐i+4 in the nonapeptide 1Y, cyclo‐(2, 6)‐( Ac ‐VKRLQDLQY‐ NH 2 ), an artificial ligand of the inhibitor of DNA binding and cell differentiation (ID) protein with antiproliferative activity on cancer cells. Herein, we show that only the cyclized five‐residue segment adopts a helical turn whereas the C‐terminal residues remain flexible. Moreover, we present nine 1Y analogs arising from different combinations of hydrophobic residues (leucine, isoleucine, norleucine, valine, and tyrosine) at positions 1, 4, 7, and 9. All cyclopeptides except one build a lactam‐bridged helical turn; however, residue‐4 reveals less helix character than the neighboring Arg‐3 and Gln‐5, especially with residue‐4 being isoleucine, valine, and tyrosine. Surprisingly, only two cyclopeptides exhibit helix propagation until the C‐terminus, whereas the others share a remarkable outward tilting of the backbone carbonyl of the lactam‐bridged Asp‐6 (>40° deviation from the orientation parallel to the helix axis), which prevents the formation of the H‐bond between Arg‐3 CO and residue‐7 NH: As a result, the propagation of the helix beyond the lactam‐bridged sequence becomes unfavorable. We conclude that, depending on the amino‐acid sequence, the lactam bridge between Lys‐i and Asp‐i+4 can stabilize a helical turn but deviations from the ideal helix geometry are possible: Indeed, besides the outward tilting of the backbone carbonyls, the residues per turn increased from 3.6 (typical of a regular α‐helix) to 4.2, suggesting a partial helix unwinding. Abstract : The NMR solution structures of several Lys i ‐Asp i+4 lactam‐bridged short helical peptides showed a significant outward tilt of the backbone carbonyls and 4.2 residues per turn.